Competition of Organic and Mineral Phases in Radiocesium Partitioning in Organic Soils of Scotland and the Area near Chernobyl - Rigol, Anna; Vidal, Miquel; Rauret, Gemma; Shand, Charles A; Cheshire, Martin V (Environmental science & technology, 1998)
Radiocesium (RCs) partitioning has been studied in four organic soils, with an organic matter (OM) content from 46 to 99%. For each soil, two fractions were derived after removing fats/waxes and humic/fulvic acids (humin + mineral) and after further removal of the mineral matter by an HF/HCl treatment (humin). Characterization by ICP−OES, FTIR, and XRD showed that the removal of mineral matter by the HF treatment was complete. Illitic material was observed in all the soils, with the exception of that with 99% OM. Two patterns of adsorption and desorption were observed. For the 99% OM soil and all the humin fractions, the increase of NH4 in the solution did not affect the RCs distribution coefficient (K D), and no differences were observed between the desorption yields obtained with CH3COONH4 and CaCl2 (around 80% for each extractant). For the other three soils and their humin + mineral fractions, an increase of NH4 led to a decrease in K D, and desorption yields were lower with CaCl2 than with CH3COONH4. This indicated that, in the latter soils, RCs was associated with specific sites in the illitic material. Finally, the increase in K D in the humin + mineral fraction as compared with the initial soil suggested that humic/fulvic acids influence RCs interaction with the mineral phase.